Study of Serum Uric Acid Levels in Essential Hypertension and its correlation with the severity of Hypertension (Indian Journal of Public Health Research & Development, 2023)
Background: Uric acid is thought to play a pathogenic role in hypertension mediated by several mechanisms suchas inflammation, vascular smooth muscle cell proliferation in renal microcirculation, endothelial cell dysfunctionetc. The study was carried to see the relationship between serum uric acid and hypertension and its correlationwith components of metabolic syndrome as it is thought that hyperuricemia is more common in hypertensivepatients probably because hyperuricemia may be also a component of metabolic syndrome.Methods: The present observational cross sectional study was conducted in the department of Medicine ina tertiary care hospital in Assam from June 2021 to May 2022. A total of 150 patients who were diagnosed ashypertensives following ACC/AHA guidelines, 2017. Newly detected hypertensives were enrolled for the study.Relevant clinical and laboratory data were recorded using proforma and statistical analysis were done accordingly.Results: 20% cases were found to be hyperuricemic in the study population out of which 67% of the cases who hadmetabolic syndrome had hyperuricaemia.Conclusion: There can be a direct relation between hypertension and hyperuricemia, hyperuricemia was foundin 20% of hypertensive cases. Serum uric acid level correlates significantly with variables like BMI, Dyslipidemia,stage 2 hypertension, which are components of metabolic syndrome. Thus, hyperuricaemia can be an index ofsuspicion for the concomitant presence of metabolic syndrome
Keywords: Hypertension, Hyperuricemia, Uric acid, AHA- American Heart Association